STRATEGI PENINGKATAN PENDAPATAN PETANI JERUK KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Ardiansyah, Ardiansyah; Hendro, Ekwarso; Yusni, Maulida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted in Kuok Subdistrict, Kampar Regency, with the aim of knowing how the strategy of Kuok orange farmers in increasing their income. The population in this study were all orange farmers in Kuok District, amounting to 250 people. While the sampling was carried out using the Slovin formula, namely the total sample size of 71 samples by proportional random sampling from each village in the Kuok sub-district, namely 13 villages. The data analysis method used is descriptive qualitative analysis method, and SWOT analysis, namely data obtained from a study. The result of this research is the farmers' strategy in increasing income is by doing side jobs and providing counseling from the government so that farmers know how to do citrus farming properly.Keywords: Strategy, and Orange Farming Busines